Decreased cholesterol efflux capacity in patients with low cholesteryl ester transfer protein plasma levels. (19th February 2014) - Scharnagl, Hubert; Heuschneider, Christina; Sailer, Sabrina; Kleber, Marcus E.; März, Winfried; Ritsch, Andreas
Abstract Background Cholesteryl ester transfer protein (CETP) has been considered as a possible target for treatment of cardiovascular disease. However, first clinical studies employing CETP inhibitors have failed to demonstrate clinical benefit. Additionally, we have previously shown that low endogenous plasma levels of CETP are associated with increased mortality in coronary artery disease (CAD) patients. We hypothesized that low CETP plasma levels are associated with decreased high‐density lipoprotein (HDL) function. Materials and Methods Serum HDL efflux capacity was measured in 154 patients of the Ludwigshafen Risk and Cardiovascular Health (LURIC) study displaying extremely low (< 0·68 μg/mL, n = 77) or high (> 2·13 μg/mL, n = 77) CETP concentrations in their plasma, respectively. The LURIC study is a prospective observational study of patients referred to coronary angiography at baseline with a median follow‐up time of 7·75 years. Primary and secondary endpoints were cardiovascular and all‐cause mortality, respectively. Results High CETP patients showed a significant increase in the capacity of their plasma to mediate cholesterol efflux from cholesterol laden macrophages when compared to the efflux capacity observed in low CETP patients (+ 5·4%, P = 0·015). As shown by multiregression analysis, the impact of CETP on cholesterol efflux capacity was independent from classical risk and lifestyle factors, as well as from lipid parameters including HDL cholesterol, LDL cholesterol and triglycerides. Conclusions Our findings indicate that low plasma concentrations of CETP might indeed lead to impaired HDL function within the reverse cholesterol transport pointing towards an atheroprotective role of CETP at least in patients with high risk of CAD.